TRAINING FOR RELEVANCE IN AGRICULTURE: A CRITICAL APPRAISAL OF THE SUB-DEGREE TRAINING PROGRAMME IN THE FORMER WESTERN STATE OF NIGERIA. - AKINBODE, I. ADEPETU; LADIPO, P. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Using Project Performance Budgeting System (PPBS) as the framework within which the agricultural change agents are operating, the study examined the adequacy of practical experience acquired by the graduates of the three schools of agriculture included in the study. It also examined the modification that would be required in the schools curricula to meet the need of project-oriented agricultural services. The data for the study were gathered from  the instructors in three schools (Ibadan and Akure Schools of Agriculture and Ibadan School of Animal Health) as well as from the administrators of agricultural programmes and field level extension workers in the former Western State of Nigeria. Practical training was found to be inadequate due to lack of equipment funds, time and experience on the part of the trainers. This in addition to the project-orientation of agricultural services (the situation in which the graduates of the schools are expected to function) call for some degree of specialization in training if the change agents are to perform effectively. Recommendations are made for the introduction of broad specialization. Specific suggestions are also made on how positive attitude towards agriculture could be inculcated into members of the public in general and into agricultural change agents- in training in particular.